Avaliação da resistência a flexão de ligas de Titânio (Ti6Al4V) soldadas com diferentes configurações pelo processo Plasma - Silva, João Paulo Lyra e (2011)
This study aimed to evaluate the mechanical properties of Ti-6Al-4V bars with 3.18mm diameter welded under different conditions to determine the optimal parameters to use of plasma welding machine comparing with specimens of nickel chrome (NiCr) welded by convectional process. Fifty specimens were divided in 5 groups (n = 10), control group (Control) with intact bars of titanium alloy, NiCrB group consisting of cast bars of NiCr and welded for brazing process; and groups welded with plasma process. Group PL3-10 using the regulation of the equipment 3A pulse and 10ms depth, Group PL3- 12: 3A pulse and 12 ms depth. Group PL3-14 3A pulse and 14ms depth. The bars were subjected to 3-bending flexural strength test. The values obtained were analyzed in the formula to achieve the bending stress (MPa). The statistical test ANOVA one way with index of significance (p <0.05) and test Tukey (p=0.05) was used. After carried out the analysis of samples under magnification to check the depth of weld penetration and fracture pattern. We conclude that the highest value was obtained from Control group followed to PL3-10. NiCrB group showed the lowest bending of flexural strength, being statistically different from the PL3-10 and PL3-12 and similar to the PL3-14.In analyzing the area of weld penetration was no statistical difference between groups (p> 0.05).